Entrepreneurship, Human Capital, and Regional Development: Labor Networks, Knowledge Flows, and Industry Growth - Baptista, Rui (Springer, 2015)
This book makes original contributions to the literature on clusters, human capital, and regional development by focusing on the link between entrepreneurship and economic growth, aiming for a better understanding of the dynamics of growth determined by the entrepreneur’s action in the regional space. The focus is therefore on critical reflection and rethinking the articulation between three levels of analysis of economic systems, namely entrepreneurship, human capital and regional development, which have not so far been perfectly articulated in the literature of reference on endogenous growth.